Value of upper gastrointestinal endoscopy for gastric cancer surveillance in patients with Lynch syndrome - Ladigan, Swetlana; Vangala, Deepak B.; Engel, Christoph; Bucksch, Karolin; Hueneburg, Robert; Perne, Claudia; Nattermann, Jacob; Steinke-Lange, Verena; Rahner, Nils; Schackert, Hans K.; Weitz, Jürgen; Kloor, Matthias; et al. (International journal of cancer, 2021)
In our study, we evaluated the effectiveness of upper gastrointestinal (GI) endoscopy as an instrument for early gastric cancer (GC) detection in Lynch syndrome (LS) patients by analyzing data from the registry of the German Consortium for Familial Intestinal Cancer. In a prospective, multicenter cohort study, 1128 out of 2009 registered individuals with confirmed LS underwent 5176 upper GI endoscopies. Compliance was good since 77.6% of upper GI endoscopies were completed within the recommended interval of 1 to 3 years. Forty-nine GC events were observed in 47 patients. MLH1 (n = 21) and MSH2 (n = 24) mutations were the most prevalent. GCs in patients undergoing regular surveillance were diagnosed significantly more often in an early-stage disease (UICC I) than GCs detected through symptoms (83% vs 25%; P = .0231). Thirty-two (68%) patients had a negative family history of GC. The median age at diagnosis was 51 years (range 28-66). Of all GC patients, 13 were diagnosed at an age younger than 45. Our study supports the recommendation of regular upper GI endoscopy surveillance for LS patients beginning no later than at the age of 30.
"First published: 15 September 2020".- Artikel-Front door
Gesehen am 23.09.2024